2013
DOI: 10.3109/10520295.2013.839827
|View full text |Cite
|
Sign up to set email alerts
|

Amelioration of Muc5b mucin hypersecretion is enhanced by IL-33 after 2-APB administration in a murine model of allergic rhinitis

Abstract: We attempted to clarify whether hypersecretion of Muc5b mucin from mouse nasal submucosal glands that is enhanced by interleukin (IL)-33 under allergic conditions can be ameliorated by administration of 2-APB. Immunohistochemistry was used to examine both the distribution of T cells in the nasal mucosa of an allergic rhinitis mouse model and expressions of IL-33 receptor ST2 and Muc5b protein in mouse submucosal gland cells. The amounts of protein and mRNA of Orai1, Muc5b, IL-4, IL-5, IL-13 and IL-33 in mouse … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…In healthy individuals, MUC5B is mainly expressed in submucosal glands whereas MUC5AC is exclusively present in goblet cells. Lin et al [13] showed that 2-aminoethoxydiphenyl borate (2-APB), a chemical that potentially inhibits intracellular calcium release through modification of TRP channels, reduced MUC5B secretion from submucosal glands whereas IL-33 enhanced its secretion into the nasal mucus of allergic rhinitis mouse models. 2-APB also reduced IL-4, IL-5, and IL-13 in nasal mucus as well as in the epithelium.…”
Section: Mucinsmentioning
confidence: 99%
“…In healthy individuals, MUC5B is mainly expressed in submucosal glands whereas MUC5AC is exclusively present in goblet cells. Lin et al [13] showed that 2-aminoethoxydiphenyl borate (2-APB), a chemical that potentially inhibits intracellular calcium release through modification of TRP channels, reduced MUC5B secretion from submucosal glands whereas IL-33 enhanced its secretion into the nasal mucus of allergic rhinitis mouse models. 2-APB also reduced IL-4, IL-5, and IL-13 in nasal mucus as well as in the epithelium.…”
Section: Mucinsmentioning
confidence: 99%
“…29,30 These processes are pivotal events in the mechanisms of AR. Therefore, based on previous studies, [31][32][33][34][35][36] we hypothesized that there might be expression of Orai1 in nuocytes, and the intervention of this protein might work in the attenuation of allergic reactions.…”
Section: Discussionmentioning
confidence: 99%
“…4c, j). Goblet cells and submucosal glands were reported to play a role in the development of CRS [20] and allergic rhinitis [21,22]. Therefore, we made experiments to determine these 2 types of cells before and after the treatment with budesonide using HE or PAS staining.…”
Section: Histological Analysesmentioning
confidence: 99%